Detecting acetone from breath using a PrFeO3-doped PANi/TiO2-coated PAN nanofiber sensor for non-invasive diabetic diagnosis - Yesildag, Nesibe; Ünsal, Ömer Faruk; Gömeç, Ramazan; Bedeloglu, Ayse Celik (My University, 2023)
Polyacrylonitrile (PAN) nanofibers doped with varying concentrations of perovskite praseodymium ferrite (PrFeO3) nanoparticles synthesized by calcination were successfully manufactured using a simple electrospinning process. The nanofibers were coated with layers of polyaniline-titanium dioxide (PANi-TiO2) combination using an air brush. The structure, morphology, and electrical characteristics of the nanoparticles and nanofibers were characterized by SEM, FT-IR, and electrical measurement methods. The results indicated that the produced nanofibers exhibited a strong in vitro interaction and selectivity against acetone gas, a biomarker of diabetes. Perovskite nanoparticle doped PAN nanofibers have shown approximately 43% change in resistance with acetone gas exposure. These findings suggest that PrFeO3-doped nanofibers hold promise as potential candidates for acetone gas sensors in non-invasive diabetes monitoring.
Keywords: Nanofiber; Acetone; Gas sensor; Non-invasive; Diabetics; Perovskites